(untitled) (Althea Medical Journal, 2023)
Background: Problems to COVID-19 are closely related to the level of knowledge and community prevention. Therefore, to overcome COVID-19, increased knowledge and prevention are needed. This study aimed to evaluate the correlation between prevention and knowledge level about COVID-19. Methods: A cross-sectional study using a convenience sampling approach was conducted in Banjar Gambang, Karangasem, Indonesia, in April 2022. The knowledge level and preventive behavior towards COVID-19 were measured using the COVID-19 Preventive Behaviors Index (CPBI) and the knowledge, attitudes, and practice toward COVID-19 (KAPCOV-19) questionnaire. The data were analyzed using SPSS software version 26.0. Results: A total of 52 respondents were included, who had excellent level of knowledge (44.2%) and moderate prevention behaviour (48.1%). A strong and significant correlation was found between the preventive index and the knowledge levels of COVID-19 (r = 0.548; p<0.001). The level of knowledge was significantly related to the level of preventive behavior (p= 0.003), as well as the education level (r = 0.323; p = 0.02) and age (r= -0.346; p=0.012). Conclusion: The level of knowledge and the individual prevention behavior toward COVID-19 are directly proportional to each other. Those who have a low level of knowledge, might affect their prevention behavior toward COVID-19, therefore, personalized socialization of COVID-19 prevention is still required.